The ABCs of Financial Education : Experimental Evidence on Attitudes, Behavior, and Cognitive Biases - Carpena, Fenella (World Bank, Washington, DC, 2017)
Financial literacy - the ability to make informed decisions regarding money - plays a critical role in ensuring both the well-being of households and the stability of the financial system. Consequently, numerous private institutions, non-profit organizations, and governments have responded by implementing financial education programs. However, empirical evidence on the efficacy of such programs provides only mixed results, and little is known about which aspects of financial education initiatives successfully enhance financial behavior and financial outcomes. The authors combined financial education with cash incentives for learning, non-compulsory goal-setting, and personalized financial counseling services to study the attitudinal, behavioral, and cognitive constraints that can stymie the link between financial education and outcomes.